Methotrexate Combined with 4-Hydroperoxycyclophosphamide Downregulates Multidrug-Resistance P-Glycoprotein Expression Induced by Methotrexate in Rheumatoid Arthritis Fibroblast-Like Synoviocytes via the JAK2/STAT3 Pathway - Kaili Qin; Kailin Chen; Wenpeng Zhao; Xiangcong Zhao; Jing Luo; Qun Wang; Chong Gao; Xiaofeng Li; Caihong Wang (Journal of Immunology Research)
Objective. Rheumatoid arthritis (RA) multidrug resistance is associated with P-glycoprotein (P-gp) overexpression. We investigated the effects of methotrexate (MTX) alone and combined with 4-hydroperoxycyclophosphamide (4-HC) on P-gp expression in fibroblast-like synoviocytes (FLSs) from patients with RA and examined the signaling pathway involved. Methods. RA-FLSs were treated with MTX, MTX + 4-HC, AG490 + MTX, or AG490 + MTX + 4-HC for 72 h. Proliferation inhibition rates were determined by MTT assay; P-gp expression was measured by flow cytometry and real-time polymerase chain reaction (RT-PCR); JAK2 and STAT3 were measured by RT-PCR and cell-based ELISA to assess STAT3 signaling. Results. MTX alone significantly induced P-gp expression and mRNA production in RA-FLSs. P-gp expression and mRNA levels were lower in the MTX + 4-HC group than in the MTX-alone group. In contrast to MTX, MTX + 4-HC reduced the STAT3 phosphorylation and downregulated JAK2 and STAT3 mRNA production. Inhibition of constitutively active STAT3 accompanied by 4-HC suppressed P-gp levels in RA-FLSs. The MTT assays revealed no significant differences in proliferation inhibition rates among groups. Conclusions. The increased anti-P-gp effect of MTX + 4-HC versus MTX alone in RA-FLSs was mediated via inhibition of the JAK2/STAT3 pathway and may have helped reverse MDR in refractory RA patients with high-P-gp levels.